Five ways BuzzFeed is preserving (or transforming) the journalistic field - Tandoc, Edson C (Journalism, 2018)
Guided by field theory and the concept of journalistic boundary work, this study seeks to examine whether BuzzFeed, a new agent in the journalistic field, is participating in the preservation or transformation of the journalistic field. This is carried out by comparing its news outputs with those of The New York Times based on the markers – or boundaries – that defined traditional journalistic practice, particularly news values, topics, sources, formats, and norms. The analysis found that while news articles produced by BuzzFeed are exhibiting some departures from traditional journalistic practice, in general, BuzzFeed is playing by the rules, which might explain its legitimation as a recognized agent in the field.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDY0ODg0OTE3NjkxNzg1